Discovery of Venezolanoconnus in Costa Rica (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2017)
Venezolanoconnus is a small glandulariine genus established by Franz (1988) to accommodate four species known to occur only in Venezuela. Jałoszyński (2012) revised Venezolanoconnus, illustrated and described its morphological structures, redefined the genus and transferred one of the Franz's species to Euconnus Thomson, 1859. Species included in this interesting genus resemble Euconnus in their general appearance and some morphological characters, but differ in the subcontiguous hind coxae, separated only by a pair of spines of the metaventral intercoxal process, single (and rudimentary) basal fovea on each elytron, and a unique structure of the aedeagus. The latter has the parameres not slender, as those in all species of Euconnus and most Glandulariini, but extremely broadened; they surround the median lobe in its proximal half and are fused to each other dorsally and meet along midline ventrally. The parameres are hyaline and their margins may be hardly discernible in ventral view; in lateral view the narrowing apical region of each paramere is well-visible, it bears several short setae distributed apically and subapically and at least partly shifted to the dorsal surface. Venezolanoconnus can also be recognized on the basis of an unusually swollen maxillary palpomere III and a very small palpomere IV; the mandibles lacking preapical teeth, the pronotum broadest behind middle, the head relatively small in relation to the pronotum and elytra, and the gradually thickened antennae.